(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The absorptive-excretory function of the liver plays a crucial role in ensuring the organ’s detoxification potential. This study investigated the state of this function in prepubertal (PP) rabbits of both sexes using a carbon tetrachloride-induced model of acute hepatitis. A chromodiagnostic test with cardiogrin was employed to assess liver function. The efficacy of Rutan was compared to that of the hepatoprotector Karsil in correcting the observed impairments. It was found that administration of carbon tetrachloride led to significant alterations in the pharmacokinetic parameters of cardiogrin, indicating a marked suppression of the absorptive-excretory function of hepatocytes. This was accompanied by hepatic hypoxia due to reduced liver blood flow. Experimental pharmacotherapy with Rutan and Karsil almost equally restored hepatic blood flow and corrected the pharmacokinetic disruptions of cardiogrin, reflecting the recovery of hepatocellular absorptive-excretory function. These findings suggest that Rutan may be a viable option for restoring liver detoxification potential and absorptive-excretory function.